Pengaruh Pengalaman, Due Professional Care dan Akuntabilitas Pada Kualitas Audit - Iswara Dewi, Ni Made Widia; Sudana, Putu (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
Audit quality represents the result of auditor performance in carrying out the task concerned. Audit quality is the result of auditor performance in carrying out the task concerned. Auditors are required to produce high audit quality so as to have a great responsibility to the parties concerned. The purpose of this study to determine the influence of experience, due professional care and auditor accountability on audit quality.Auditors are required to produce high audit quality so as to have a great responsibility to the interested parties. Populations in this study are all auditors who work at Public Accounting Firms in Bali. Respondents are selected using purposive sampling method, and the numbers of samples are 55 respondents. Data were collected by survey questionnaires. Data are analysed using multiple linear regressions. Based on the results of analysis, this study concluded that auditor?s experience, due professional care and accountability has a positive impact on audit quality.Based on the analysis results found that experience, due professional care and accountability have a positive and significant impact on audit quality. This indicates that the higher the experience of the auditor will be the more accountable the decision will be made. The careful use of due care carefully will provide reasonable assurance to the auditor to provide an opinion that the financial statements are free from material misstatements, whether caused by fraud or mistakes. Whereas if the accountability possessed by a high auditor then the results of audits made an auditor can be accounted for. Keywords: Experience, Due Professional Career, Auditor Accountability, Quality Audit